GHSR MODULATION BY LEAP2 IN PERINATAL PHASES IMPACTS GLUCOSE OVERLOAD RESPONSIVENESS IN YOUNG RATS (Arquivos do Mudi, 2023)
GHSr signaling is involved in the regulation of energy homeostasis. LEAP2, a recentlydiscovered peptide hormone, counteracts the effects of ghrelin. This study sought to evaluatethe effects of perinatal LEAP2 exposure in young rat offspring. For this, two protocols weredesigned to assess the roles of GHSr antagonism during the pregnancy and during thelactation. Sex-specific impacts on AUC and peak-responses of glucose tolerance tests werepresented. However, no differences were detected in the blood glucose of mixed meal fedanimals. In conclusion, perinatal LEAP2 exposure could impact the glucose-stimulatedinsulin secretion in young rats.